2019
DOI: 10.1080/03602532.2019.1632891
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenes: cytochrome P450 oxidation and mechanism-based enzyme inactivation

Abstract: The oxidation of carbon-carbon triple bonds by cytochrome P450 produces ketene metabolites that are hydrolyzed to acetic acid derivatives or are trapped by nucleophiles. In the special case of 17αethynyl sterols, D-ring expansion and de-ethynylation have been observed as competing pathways. The oxidation of acetylenic groups is also associated with mechanism-based inactivation of cytochrome P450 enzymes. One mechanism for this inactivation is reaction of the ketene metabolite with cytochrome P450 residues esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…The authors utilized various in vitro tools to determine the irreversible inhibition mechanism of ICT with CYP3A. It has been reported that oxidation of acetylenic groups can lead to inactivation of CYPs ( Ortiz de Montellano 2019 ). From their mechanistic studies, the authors proposed that the acetylene moiety of ICT was metabolically activated, and the resulting ketene intermediate was responsible for heme destruction and the observed CYP3A enzyme inactivation.…”
Section: Commentarymentioning
confidence: 99%
“…The authors utilized various in vitro tools to determine the irreversible inhibition mechanism of ICT with CYP3A. It has been reported that oxidation of acetylenic groups can lead to inactivation of CYPs ( Ortiz de Montellano 2019 ). From their mechanistic studies, the authors proposed that the acetylene moiety of ICT was metabolically activated, and the resulting ketene intermediate was responsible for heme destruction and the observed CYP3A enzyme inactivation.…”
Section: Commentarymentioning
confidence: 99%
“…The acetylenes are initially oxidized either to a ketene intermediate (for terminal acetylenes) (Sridar, et al, 2012;Zhao, et al, 2018) or an oxirene intermediate (for internal acetylenes). Both these intermediates can either alkylate heme or the apoprotein depending upon the overall structure of the inactivator (Ortiz De Montellano, 2019;Roberts, et al, 1998;Roberts, et al, 1993;Roberts, et al, 1994). More recently, sulfenylation of the heme thiolate has been observed for CYP4A11 and may be involved in the modification of catalytic activity (Albertolle, et al, 2017).…”
Section: Heme Destruction/modificationmentioning
confidence: 99%
“…TDI drugs have different mechanisms of CYP inactivation depending on the functional group present on the drug (Fontana, et al, 2005;Hollenberg, 2002;Kamel & Harriman, 2013;Orr, et al, 2012;Ortiz De Montellano, 2019). Some of the notable functional groups that inactivate CYPs are methylenedioxy aromatic groups, acetylenes, alkyl and aryl olefins, thiophenes, amines, furans, and phenols (Kalgutkar, et al, 2007;Kalgutkar & Soglia, 2005;Zhou, et al, 2004).…”
mentioning
confidence: 99%
“…About 300,000 CYP sequences have been collected from public and private sources ( Nelson, 2018 ). The common reactions catalyzed by CYPs include hydroxylation, heteroatom oxygenation and release, epoxidation, and oxidation of double, triple, or aromatic π-bonds ( Guengerich, 2001 ; McIntosh et al, 2014 ; Ortiz de Montellano, 2019 ). Mammalian CYP enzymes are distributed in a variety of tissues and organs of organisms, and play a core role in cell metabolism to maintain cell homeostasis mainly by mediating the metabolism of a large number of xenobiotic and endobiotic molecules, including but not limited to drugs, industrial toxins, steroids, cholic acid, and fatty acids through regio-, chemo- and stereospecific oxidation, peroxidation and reduction ( Urlacher and Girhard, 2012 ; Manikandan and Nagini, 2018 ).…”
Section: Introductionmentioning
confidence: 99%